An overview of ethno-dietary plants in India: a review based on outcomes of ethnomedicinal studies by CCRAS and their validation through Ayurvedic and ethnomedicinal literature - Venigalla, Sridevi; Vallepu, Nagaraju; Kanagaraj, Vairamuthu; Palakuru, Hema Raju; Jalajakumari Padmanabhan, Iswarya Lekshmi; Goli, Penchala Prasad; Nagayya, Shiddamallayya; Govindarajan, Nartunai; Narayanam, Srikanth; Acharya, Rabinarayan (Ethnobotany Research and Applications, 2026)
Background: India’s ethnomedicinal heritage reflects a unique interplay of biodiversity, culture, and science, warranting conservation and research. Indigenous communities rely on local plants for nutrition and healthcare, yet ethnic foods remain understudied. This inventory study of ethno-dietary plant species among indigenous peoples in India and validates them using Ayurvedic and ethnomedicinal literature. Methods: The data for this study is based on the ethno-dietary information enumerated in 17 books and 50 papers published by the Central Council for Research in Ayurvedic Sciences (CCRAS), New Delhi, from 1972 to 2023. Results: The study documented 681 ethno-dietary taxa across 445 genera and 137 families. Fabaceae (59 species) was dominant, and herbs (249 species) were most used. Leading genera were Solanum (17), Ficus (11), and Dioscorea (10). Of these, 133 plants are cited in Ayurveda, indicating long-standing influence on indigenous diets. Bambusa bambos (L.) Voss, Centella asiatica (L.) Urb., and Chenopodium album L. demonstrate the highest Relative Frequency of Citation (0.15); Bambusa bambos (L.) Voss, Ficus auriculata Lour., and Rotheca serrata (L.) Steane & Mabb. exhibit high Relative Use Value (0.45); and Amaranthus spinosus L., Amorphophallus paeoniifolius (Dennst.) Nicolson, Chenopodium album L., and Solanum nigrum L. shows 100% Plant Part Value. Conclusions: The present study on the review of ethno-dietary plant species will aid in preparation of a comprehensive database of wild edible plants among different parts of India, thereby understanding the culturally acceptable species which hold significant potential as resources for nutraceutical bioprospecting and need of conservation. Keywords: India; Ethnodietary; relative frequency of citation; relative use value; plant part specificity; ethnic community, dietetic diversity